What difference could Pragmatism have made? From architectural effects to architecture’s consequences - Pauline Lefebvre (Footprint)
By the late 1990s, the once fruitful alliance between architecture and continental philosophy was perceived as being responsible for the apparent schism between architectural theory and practice. In that context, some saw Pragmatism as a potential alternative for reviving the architectural discourse. This paper first considers how this enterprise was actually more of a continuity than rupture with former philosophical affinities. The introduction of Pragmatism in architecture was discussed in the same breath as previous developments based on Deleuze and Foucault, mostly around the ‘diagram’. Architectural thinkers were then following the recent revival of Pragmatism in American philosophy, carried out by figures like Rorty, and based on a reconciliation between American Pragmatism and Continental philosophies. This might explain why they favoured Pragmatism at the expense of contemporary analytic philosophy. This also explains why their initiative was not as successful as they expected: the alternative did not appear as offering enough of a contrast. In the second part of the paper, I take this non-fulfilment as an opportunity to explore – to speculate – what Pragmatism could have contributed to the ‘post-critical’ scene that followed in the early 2000s. The main post-critical move is a shift away from ‘meaning’ towards the material, sensuous ‘effects’ of architecture. Pragmatism appeared relevant, as its main gesture is to consider effects rather than causes and to dismiss all discussions that have no practical bearings. But Pragmatism has more to offer than just a refocus on practice. My hypothesis is that Pragmatism expands the obligations of architecture. It doesn’t just bring to the fore concrete, seductive ‘effects’ of buildings; it also insists on considering their broader ‘consequences’ on the environment – physical as well as social and cultural – and on inventing ways of dealing with them.